Faktor yang Memengaruhi Kualitas Layanan Administrasi Akademik - Nasution, Samsinar (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
The quality of administrative staff services will increase student satisfaction and increase the university's superiority in competition. Increasing employee motivation and performance, or their work performance, is one of the efforts that is expected to improve the quality of administrative services. This research aims to determine the relationship between the motivation of administrative employees and their performance on the quality of academic administration services at UIN Syahada Padangsidimpuan. The actual condition of the variable quality of academic administration services within the Academic Directorate of UIN Syahada Padangsidimpuan can be seen from the highest sub-variable, namely the reliability sub-variable. The second sub variable is the tangible sub variable. The third sub variable is the assurance sub variable. The fourth sub variable is responsiveness and the lowest is the empathy sub variable. Motivation has a positive and significant effect on the quality of academic administration services at the Academic Directorate of UIN Syahada Padangsidimpuan by 16.18%. The performance of administrative employees has a positive and significant effect on the quality of academic administration services at the Academic Directorate of the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University by 30.03%. Overall, the motivation and performance of administrative employees regarding the quality of academic administration services at the Academic Directorate of the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University is 86.9%. The remaining 13.1% is the influence that comes from other factors.